Designing a Student Counseling Guidance Information System at SMA Negeri 1 Batang Kapas Using the Codeigniter (CI) Framework - Citra, Reka Sabna; Zakir, Supratman (Knowbase : International Journal of Knowledge in Database, 2021)
This research is conducted because of the need for an information system about how each student's learning development and student behavior were needed, so that Counseling Teacher (BK) was needed. Counseling Teacher (BK) SMA Negeri 1 Batang Kapas is a school directly related to student discipline that requires a computerized information system to operate data collection so that it is more optimal. It is carried out because the Counseling Guidance in schools has not used a computerized system in carrying out its work activities, the school still uses a conventional system such as in making attendance reports and archiving student violation data still using a portfolio so it seems that they use a lot of paper, many points of violation are not accumulated because of recording is still manual, so that sanctions are not appropriate and there is no valid and effective database in data management. It is the background for researchers to design a student counseling guidance information system using the CodeIgniter (CI) framework. The methodology used in the research is the type of research and development research commonly called R&D, which is research to create the desired program and test the program's effectiveness. The research model chosen is the 4D version, namely define, design, develop, and disseminate. This model uses the waterfall. Based on the results of the product test, the validity results of several computer experts were 0.91 (very valid), the results of the practicality test of two Counseling Teacher and one homeroom teacher obtained an average result of 0.91, which is very practical, while for the effectiveness test it was obtained value 0.91 (very high).